Pengaruh Deskripsi Pekerjaan, Disiplin Dan Etika Kerja Terhadap Prestasi Kerja Aparatur Sipil Negara (Asn) Pada Kantor Sekretariat Dprd Provinsi Sumatera Utara - Sri Puspa Dewi; Sinto Sinto; Asmaul Husna (Universitas Islam Sumatera Utara, 2022)
This research was conducted at the secretariat of the DPRD of North Sumatra Province, where the purpose of this study was to determine the extent to which job description, discipline and work ethics, both partially and simultaneously affect the work performance of employees within the secretariat of the DPRD of North Sumatra Province. This study used quantitative methods, where the population in this study was 46 employees, and the sample taken was as much as 100% of the total population because the number was not up to 100 people. The results of this research show that partially the job description variable (X1) and work ethic variable (X3) have a significant effect on employee work performance within the secretariat of the DPRD of North Sumatra Province (Y), with a t calculate value of 2.194 and a significance level value of 0.003 smaller than 0.05 partially the job description (X1) has a significant effect on the work performance of employees within the secretariat of the DPRD of North Sumatra Province (Y), and a t calculated value of 3.835 and a significant level of 0.000 smaller than 0.05 partially work ethics (X3) has a significant effect on the work performance of employees within the secretariat of the DPRD of North Sumatra Province (Y). Meanwhile, simultaneously, both job description (X1), discipline (X2) and work ethics (X3) have a significant effect on the work performance of employees within the secretariat of the DPRD of North Sumatra Province, with a F calculated value of 7,351 and a significant level value of 0.000 less than 0.05